Pattern and Outcome of Childhood Cancer in Rivers State University Teaching Hospital - Tamunoiyowuna G. Okari; Boma A. West; Woroma Wonodi (Archives of Current Research International, 2020)
Introduction: Childhood cancer is on the increase globally with a heterogenous distribution in the type seen in different localities, age groups, and gender. So also, is the outcome of treatment variable in different countries and is dependent on the availability of funds, drugs, medical equipment among others. Aim: To determine the pattern and outcome of childhood cancer in Rivers State University Teaching Hospital (RSUTH). Methods: A 5-year retrospective study was carried out in RSUTH from January 2015 to December 2019. The case notes of all children aged 1-16years with diagnosis of childhood malignancy were retrieved and only those with histopathologic diagnosis of cancer and complete data were included in the study. Results: Thirty-two children aged 1-16years, with a median age of 6years, 24 (75%) males and 8 (25%) females were recruited for the study. The median duration of symptoms was 3 months. Majority of the care givers (75%) were of low socio-economic class. Leukaemia 8 (25%) and lymphomas 5 (18.8%) were the common malignancies seen and 50% had metastatic disease at presentation. Fever (62.5%), weight loss (56.3%) and pallor (46.9%) were common complaints given, while chemotherapy alone 5 (15.6%) or in combination with surgery 5 (15.6%) was the most given treatment. Three (9.4%) children completed treatment and are alive, 28.1% requested for discharge against medical advice and 28.1% died. Conclusion: Leukemia and lymphomas are common forms of childhood malignancy in our facility. Majority of the caregivers were poor and unable to complete the required treatment of their children.